The association of morning serum cortisol with glucose metabolism and diabetes: The Jackson Heart Study. (May 2019) - Ortiz, Robin; Kluwe, Bjoern; Odei, James B.; Echouffo Tcheugui, Justin B.; Sims, Mario; Kalyani, Rita R.; Bertoni, Alain G.; Golden, Sherita H.; Joseph, Joshua J.
Highlights: Examined the role of serum cortisol in glycemia and T2D in African Americans (AAs). Cortisol was associated with dysglycemia and insulin resistance, modified by adiposity. Quartile 4 vs. 1 of serum cortisol was associated with a 1.26-fold higher T2D odds. These findings support a role for morning serum cortisol in glycemia among AAs. Abstract: Background: Serum cortisol levels have been associated with type 2 diabetes (T2D). However, the role of cortisol in glycemia and T2D is not fully elucidated among African Americans (AAs). We hypothesized that among AAs morning serum cortisol would be positively associated with glycemic measures and prevalent T2D. Methods: We examined the cross-sectional association of baseline morning serum cortisol with fasting plasma glucose (FPG), hemoglobin A1c (HbA1c), homeostasis model assessment of insulin resistance (HOMA-IR), β-cell function (HOMA-β), and prevalent T2D in the Jackson Heart Study. Linear regression models were used to examine the association of log-transformed cortisol with glycemic traits, stratified by T2D status. Logistic regression was used to examine the association of log-transformed cortisol with prevalent T2D. Models were adjusted for age, sex, education, occupation, systolic blood pressure, waist circumference, physical activity, smoking, beta-blocker/hormone replacement medications and cortisol collection time. Results: Among 4, 206 AAs (mean age 55 ± 13 years, 64% female), 19% had prevalent T2D. A 100% increase in cortisol among participants without diabetes was associated with 2.7 mg/dL (95% CI: 2.0, 3.3) higher FPG and a 10.0% (95% CI: -14.0, -6.0) lower HOMA-β with no significant association with HbA1c or HOMA-IR. In participants with diabetes, a 100% increase in cortisol was associated with a 23.6 mg/dL (95% CI: 13.6, 33.7) higher FPG and a 0.6% (95% CI: 0.3, 0.9) higher HbA1c. Among all participants, quartile 4 vs. 1 of cortisol was associated with a 1.26-fold (95% CI: 1.75, 2.91) higher odds of prevalent T2D. Conclusion: Higher morning serum cortisol was associated with higher FPG and lower β-cell function among participants without T2D and higher FPG and HbA1c in participants with diabetes. Among all participants, higher cortisol was associated with higher odds of T2D. These findings support a role for morning serum cortisol in glucose metabolism among AAs.